Influence of the subsurface physical barrier on nitrate contamination and seawater intrusion in an unconfined aquifer - Ke, Shengnan; Chen, Jiajun; Zheng, Xilai (Environmental pollution (1987), 2021)
Coastal areas are facing not only environmental problems associated with seawater intrusion (SWI) but also health and ecological problems caused by excessive nitrate (NO3−) contamination. The installation of a subsurface physical barrier (SPB) is one of the common methods employed to reduce or prevent SWI, but there are few studies on the impact of SPBs on NP in groundwater. Through laboratory experiments and numerical simulations, the effects of the hydraulic gradient (HG), the nitrate concentration of the set groundwater nitrate pollution source, the relative height of the SPB (HP’) and the relative distance between the SPB and the saltwater boundary on the NP of groundwater in the presence of SWI, subsurface dams and cut-off walls were studied. Evaluation indicators were established to evaluate the degree and shape of the SWI and NP. To better describe the relationship between the velocity distribution and changes in the velocity distribution area and the degree of NP and SWI, the velocity distribution in the presence of SWI and a SPB was summarized separately. The results showed that when there was SPB, low-velocity zones were formed on both sides of the SPB, which not only slowed the migration of NO3− but also changed the shape of the NO3−-contaminated area. The closer to the SPB area the pollutants were, the more obvious the obstruction effect. The obstruction effect of adding the cut-off wall on NP was more obvious than that of adding the subsurface dam wall. The selected HG and Hp’ were important factors affecting NP and SWI. The higher HG was, the more serious the NP, the lower the HG, and the stronger the degree of SWI. Adding SPBs reduces the impact of HGs on NP and SWI. Therefore, the design of SPBs in coastal areas should focus on aspects related to these two factors. [Display omitted] •Both SWI and the subsurface physical barrier (SPB) delayed NP.•Flow velocity zoning in the presence of SWI and the SPB was generalized respectively.•Hydraulic gradients and relative height of SPBs were key factors affecting NP or SWI.•Obstruction effect of cut-off walls on NP was more obvious than subsurface dam walls.•Adding SPBs reduces the impact of HGs on NP and SWI.